If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2x + 3 = x + -8 + 11 Reorder the terms: 3 + 9x + -2x = x + -8 + 11 Combine like terms: 9x + -2x = 7x 3 + 7x = x + -8 + 11 Reorder the terms: 3 + 7x = -8 + 11 + x Combine like terms: -8 + 11 = 3 3 + 7x = 3 + x Add '-3' to each side of the equation. 3 + -3 + 7x = 3 + -3 + x Combine like terms: 3 + -3 = 0 0 + 7x = 3 + -3 + x 7x = 3 + -3 + x Combine like terms: 3 + -3 = 0 7x = 0 + x 7x = x Solving 7x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7x + -1x = x + -1x Combine like terms: 7x + -1x = 6x 6x = x + -1x Combine like terms: x + -1x = 0 6x = 0 Divide each side by '6'. x = 0 Simplifying x = 0
| 2x-3+4=0 | | 2*5+1+4c-3=40 | | (2a+3b)(3a+2b)= | | 5*6-1+3b+4=48 | | 9x/5=18 | | 2a+6+5a-4=44 | | 2a+6b-5a-b+1= | | 9x+13y=12000 | | x/6-5/8=7/8 | | -4(6s-2)=16 | | 8*4/7 | | 1.9(1/4)= | | 18n-5=6n+19 | | 3p-3=4p-7 | | 5/1/6(-2/5)= | | P=18+2x | | 234=-2/5x | | 4x-6-6x+4=0 | | 9x^(-1/2)=x^(1/6) | | 33=(2w-5)*w | | 33=w*(2w-5) | | 7a+5=5 | | 10-(w+3)-4w+5=w-12 | | 5[x+4]=35 | | cos(6x)+4cos(2x)=0 | | 35=w*(2w-5) | | 4x^3+2x=1 | | -7x-6y=-22 | | X^2/2=110 | | A=(28)(15) | | 14g+10.5g-19.58=-3(-15.3g-18.44) | | 8-3n=-19 |